Boron Neutron Capture Therapy: From Nuclear Physics to Biomedicine - Silva Bortolussi; Yuan-Hao Liu; Ignacio Porras (Biology, 2021)
Boron Neutron Capture Therapy (BNCT) is a binary radiation treatment exploiting a nuclear reaction occurring in tumor cells [...]